Modification of poly(butylene succinate) with biodegradable glycolic acid: Significantly improved hydrolysis rate retaining high toughness property. Issue 19 (30th December 2021) - Ding, Yue; Wang, Jingxi; Luo, Congcong; Yao, Bing; Dong, Liming; Du, Xihua; Ji, Junhui
Abstract: Marine microplastic pollution damages the marine biodiversity and endangers human health. Poly(butylene succinate) (PBS) is considered a biodegradable polyester; however, PBS has a slow degradation rate in seawater. In this research, glycolic acid (GA) segments were introduced in PBS main unit via melt polycondensation. The number‐average weight of PBSGA copolymer ranged from 3.1 to 4.1 × 10 4 g mol −1 with GA contents of 0%–40%. PBSGA possessed excellent mechanical properties and thermal stability. The tensile strength was 6 40 MPa, the elongation at break was more than 220% and the thermal decomposition temperature was high than 380°C. It was also found that the weight loss of PBSGA copolymer showed a tendency of alkaline > lipase > acidic > neutral > salt. In alkaline solution, the PBSGA copolymer completely decomposed after 21 days. In acidic and neutral solution, the increase of GA content improved the degradation rate of copolymer. In phosphate buffered solution, lipase accelerated the rate of ester bonds hydrolysis; however, salt had the opposite effect in NaCl solution. Thus, by introducing easily hydrolyzable GA groups, seawater degradable materials can be obtained to overcome the unfavorable factors of seawater environment. Abstract : Glycolic acid units in the PBSGA copolymers excellent improve the hydrolysis rate of copolymers. Enzymes play a catalytic role in the degradation of polyester, while salt plays an inhibitory role.